Eight caring technology principles: development and implementation of a framework for responsible health technology innovation - Tania Moerenhout; Hilde Vandenhoudt; Walter Daems; Lara Vigneron; Tinne Vandensande (Journal of Responsible Innovation)
Successfully implementing care technology to enhance people's health-related quality of life poses several challenges. Although many technological tools are available, we lack consensus on values and principles, regulatory systems, and quality labels. This article describes the FIDE process of the Belgian ‘Teckno 2030' project: Future-thinking Interdisciplinary workshops for the Development of Effectiveness principles, resulting in a framework of eight Caring Technology principles. These principles are built on three overarching values: autonomy, justice, and trust. The framework enables responsible health technology innovation by focusing on the needs of users and society, data security, equity, participatory governance, and quality control. A learning community was established to support the framework’s implementation in projects, organizations, and the broader innovation community. We also discuss the barriers, facilitators, and practical tools developed within this learning community. The FIDE process, caring technology principles, and learning community provide a case study for responsible innovation in care technology.